Application of Authentic Assessment In Arabic Language Teaching In The Program of Studying The Arabic Language At The Idrisi Islamic Boarding School For Boys, Jember: تطبيق التقييم الواقعي في تعليم اللغة العربية في برنامج دراسة اللغة العربية بالمعهد الإسلامي الإدريسي للبنين جمبر - Muhammad Nidom Hamami Abicandra (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
Often, a teacher evaluates the learning process only after the overall process is completed and generally only measures students' cognitive abilities, while other skills cannot be calculated. The purpose of this study is to describe the application of authentic assessment using the model of report and presentation (appearance) in the language program Boarding school APIS Al Idrisy 2 Jember and describe the effectiveness of the application of authentic assessment using the model of report and presentation (appearance) in improving the process and outcome of learning Arabic in the language Program Boarding School APIS Al Idrisy 2 Jember. This study uses an action research design that focuses on in-class activities, so the investigation is a class action consisting of two cycles. This study was held in the language program Boarding school APIS Al Idrisy 2 Jember at the level of wustha. This study shows the effectiveness of student reports and presentations in improving the quality of processes and outcomes in learning Arabic. كثيرا ما يقع في عملية التعليم، أن المدرس يُجري التقويم في نهاية عملية التعليم فقط، ويقوّم أو يكشف المستوى الإدراكي الطلاب فحسب، وأما الكفاءات الأخرى عند الطلاب فغير مكشوفة. هذه الدراسة هي دراسة إجراء العملي الصفي في عملية تقويم الطالب عند تعليم اللغة العربية في برنامج دراسة اللغة العربية بالمعهد الإسلامي الإدريسي للبنين جمبر بتطبيق التقييم الواقعي من خلال التقرير وتقديم العرض. وذلك بهدف إلى وصف التطبيق مدى فعالية نظام التقييم الواقعي في تعليم اللغة العربية من خلال التقرير وتقديم عرض الطلاب في برنامج دراسة اللغة العربية بالمعهد الإسلامي الإدريسي للبنين جمبر. مجتمع هذه الدراسة على طلاب الصف الوسطى في برنام ج دراسة اللغة العربية بالمعهد الإسلامي الإدريسي للبنين جمبر. واستعان الباحث في هذه الدراسة بالمقابلة الشخصية التي أجراها مع مدير المعهد، والملاحظة، والاستبانة الموجهة إلى معلم اللغة العربية والطلاب، وكذلك المذكرة الميدانية والوثائق. وتوصلت هذه الدراسة إلى نتائج تتخلص أهمها أن تطبيق تقويم الشامل من خلال التقرير وتقديم العرض عند الطلاب له الفعالية لمدى تحسين نوعية نتيجة تعلم الطلاب والتعليم، ولكشف الكفاءات الحقيقية لدى الطلاب في مدى استيعاب المهارات اللغوية، وإن التوظيف بكتابة التقرير مع القيام بالملاحظة ثم تقديمه عرضا يؤدي إلى ارتقاء الدافعية ورغبة الطلاب عند عملية تعليم اللغة العربية.